(untitled) (The Pakistan Development Review, 2013)
Pakistan has plunged into darkness because of severe electricity shortage over the last few years. The electricity shortfall has reached 4,250 MW with demand standing at 16,400 MW and generation at 12,150 MW in June 2013 (PEPCO). The load shedding and power blackouts act as a binding constraint to the economic growth through their impact on employment, trade and poverty [Kessides (2013)]. The existing statistics reveal that Pakistan has witnessed low GDP growth rate during the periods of low or negative electricity growth and during the periods where electricity growth picked up there is an increase in GDP growth rate [Pakistan (2013)]. The power crisis has destroyed the industrial sector of Pakistan. Around 40 percent factories and industry units have now been closed and around 7.5 percent of labour force is out of jobs only because of this dilemma.1